PERKEMBANGAN KONSUMSI TERIGU DAN PANGAN OLAHANNYA DI INDONESIA 1993-2005 - Hardinsyah Hardinsyah; Leily Amalia (Jurnal Gizi dan Pangan, 2007)
The objective of this study was to analyze trend of wheat flour consumption and its processed products in Indonesia since 1993 until 2005.  The data used were food consumption data of Socio-economic Survey (SUSENAS) collected by Statistics Indonesia (Badan Pusat Statistik, BPS). The results showed that the wheat flour consumption and its processed products tended to increase from 1993 to 2005. The rapid increase was occurred in the period of 1993-1996 and 1999-2005.  Three kinds of wheat flour-processed products that significantly increased were instant noodle, fried food and snack for children.  The average consumption level of wheat flour and their processed products in 2005 in urban areas were higher than the consumption level in rural areas, namely 47.7 vs. 36.3 g/cap/d.  Among all of the wheat flour-processed food, wheat flour based-fried food, instant noodle, and noodle with meat ball (mie bakso) were the most three popular kind of wheat flour processed products consumed by Indonesian people, 49.4, 48.6 and 44.7% respectively. The consumption pattern was relatively similar between urban and rural areas.  It indicated that wheat flour processed food had already been a part of food consumption pattern of Indonesian people.